Teen Social Interactions and Well-being during the COVID-19 Pandemic - Charlene Marie Kalenkoski; Sabrina Wulff Pabilonia (Global Labor Organization (GLO), 2023)
Adolescence is an important developmental period when teens begin spending less time with their parents and more time with friends and others outside their households as they transition into adulthood. Using the 2017-2021 American Time Use Surveys and the 2012, 2013, and 2021 Well-being Modules, we examine how the time teens spent alone and with parents, friends, and others changed during the COVID-19 pandemic, shedding light on how the social isolation of the pandemic disrupted this crucial development period. We also examine how time spent on various activities changed during the pandemic. Teens spent more time alone during the pandemic than before and spent more of their leisure time alone, with large increases in time spent playing computer games, on social media, and watching TV. Results suggest that socializing and communicating with others improves teens' well-being over other activities. Thus, teens' well-being was severely impacted by the pandemic.
Keywords: J13; J22; 330; teens; adolescents; COVID-19; well-being; time use; gaming